Latin and Fundamentals of Medical Terminology : Handbook for the І st year English-Speaking Students of the Medical Faculties - Тітієвська, Тетяна Василівна; Гордієнко, Олена В'ячеславівна; Куліченко, Алла Костянтинівна; Мартьянова, Марія Євгеніївна; Titiyevska, T.; Gordiyenko, O.; Kulichenko, A.; Martianova, M. (Zaporizhzhia state medical university, 2016)
The handbook is made up for the І st year English-speaking students of the medical faculties who want to master medical Latin. Each structural unit contains a detailed grammatical explanation, the examples of anatomical, histological, clinical and pharmaceutical terminology, oral and written exercises to give maximum opportunity for the students to practice. Some units include the vocabulary used in the exercises to give the students an extra help at each step.
Латинська мова та основи медичної термінології : навч. посіб. для студ. – іноземних громадян І курсу мед. ф-тів